An amphiphilic poly(vinylidene fluoride)-b-poly(vinyl alcohol) block copolymer: synthesis and self-assembly in water. Issue 7 (18th January 2017) - Guerre, Marc; Schmidt, Judith; Talmon, Yeshayahu; Améduri, Bruno; Ladmiral, Vincent
Abstract : This study is the first report of the synthesis and self-assembly in water of an amphiphilic PVDF- b -PVA block copolymer. Abstract : This study is the first report of the synthesis and self-assembly in water of an amphiphilic PVDF- b -PVA block copolymer. The block copolymer was prepared by sequential RAFT polymerization of VDF and VAc followed by saponification of the PVAc block and was characterized by 1 H NMR and FTIR. The self-assembled nanoparticles were characterized by DLS and cryo-TEM.